Denominational Publishing in Early Canada: Two Unitarian Periodicals - MacDonald, Mary (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherche et d’étude sur le livre au Québec, 2010)
Religious denominations were responsible for a large percentage of early Canadian periodical publishing. In a study of two mid-nineteenth century Montreal Unitarian periodicals the author demonstrates that such periodicals conformed to the standard communications circuit but, owing to the emphasis on theology rather than on profit, provided variations at each point: authors were not paid, printers were members of the denomination, distribution was through a network of sympathizers, and, despite the circulation of free copies, readers were most often the already-converted. As do other religious periodicals, the two Montreal periodicals provide an insight into the life of their community, as well as into the personal and publication networks, both local and international, of their denomination.